Kebijakan Keamanan Siber dan Kedaulatan Data: Suatu Kunci Dalam Mewujudkan Digitalisasi Pemilu di Indonesia - Suprayitno, Dede; Indrawan, Jerry; Hartanto, Hartanto; Yuliandri, Putrawan (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
Technological advances require Indonesia to transform. In elections, technological advances seem to demand promising changes. Indonesia has also implemented digitalization of elections in stages, starting with the Voter Data Information System (SIDALIH) and the Vote Counting System (SITUNG). This study is peeled through a qualitative approach with a descriptive method. This technique is used to parse research topics and create descriptions in a systematic, factual and accurate manner based on literary sources. The results of the study state that Indonesia has started digitizing elections and has made developments from time to time. The digitization of elections is also an urgent need to improve the quality of democracy in the country and economic efficiency. To support this, it is necessary to strengthen the digitization of elections. Among them are strong cyber security policy regulations to support data sovereignty, strengthening information technology infrastructure that is evenly distributed and the readiness of human resources which is realized by increasing digital literacy.